Digitizing Halal Tourism and Designing Muslim-Friendly Tourism Categorization as an Effort to Minimize Uncertainty in Halal Tourism in Blitar Raya - Moh Farih Fahmi; Moch Khoirul Anwar; Sri Abidah Suryaningsih; Arasyi Fahrulloh; Clarashinta Canggih; Rahmad Syaifudin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Halal tourism in practice is still full of uncertainty. This is due to inconsistency from Muslims, especially in Blitar Raya. This article will discuss three issues, the first is about why halal tourism is still full of uncertainty, the second is designing a Muslim-friendly tourism categorization that supports the implementation of Muslim-friendly tourism and the third is discussing the digitalization of quality Muslim-friendly tourism. This research uses a qualitative method with a mixed approach. The first result of this research is that Muslim-friendly tourism has a high level of uncertainty and causes inconsistencies. Second, uncertainty regarding Muslim-friendly tourism can be minimized by categorizing Muslim-friendly tourism starting from the red, yellow and green categories. Third, this categorization needs to be supported by digitalization to encourage the availability of Muslim-friendly tourism in Blitar Raya.